IMPLEMENTATION OF IRRIGATION DEVELOPMENT PROGRAMS IN VILLAGES MALLINRUNG, LIBURENG DISTRICT, BONE REGENCY - Arsal, Achmad Rafi; Aslinda, Andi; Ismail, Ismail (Universitas Negeri Makassar, 2025)
This research aims to determine the implementation of the Irrigation Development Program in Mallinrung Village, Libureng District, Bone Regency. This research uses a qualitative approach and produces descriptive data. Data collection was carried out using observation, interview and documentation techniques. The data analysis technique used consists of data condensation, data presentation, and drawing conclusions. The results of the research show that, the implementation of the irrigation network system development policy in Mallinrung Village has not run optimally due to the lack of adequate resources to support the implementation of the policy. The theory used in this research is George C. Edward III's theory of public policy implementation with indicators. Communication, Resources, Disposition, and Bureaucratic Structure. Good cooperation to overcome irrigation management obstacles between water-using communities still allows policy implementation to proceed. The disposition is quite good where policy implementers carry out maintenance, upkeep of infrastructure and supervision to the maximum. Limitations in implementing technical instructions for farmers so that participation in following the specified tasks and functions still needs to be improved. The bureaucratic structure has been clearly defined, the main challenge lies in the understanding and participation of farmers in implementing the policy